KREATIVITAS DALAM PEMBELAJARAN PKN DAN IPS MASA NEW NORMAL: LEARNING MEDIA COMBINATION BERBASIS SOCIAL LEGACY - Purwatiningsih, Ary; ., Prayetno; Mulianingsih, Ferani (Harmony: Jurnal Pembelajaran IPS dan PKN, 2020)
The purpose of this community dedication is to provide provisions for the implementation of online Civics and Social Sciences learning at home in Junior High School students as a result of the COVID-19 pandemic. This dedication uses a situation analysis where in gathering the data information about Civics and Social Sciences learning in the middle of the relevant Covid-19 Pandemic. The result of community dedication showed that the impact of COVID-19 on Civics and Social Sciences online learning in Junior High School has not been implemented well enough. It can be seen from the readiness of the implementation of Civics and Social Sciences online learning in Junior High Schools, as well as creativity in learning Civics and Social Sciences during the new normal period carried out by teachers must be improved. While learning in the new normal period is very much needed collaboration between teachers, students and parents in learning at home. Pengabdian masyarakat ini bertujuan untuk memberi bekal implementasi pembelajaran PKn dan IPS daring dirumah pada peserta didik jenjang Sekolah Menengah Pertama akibat dari adanya pandemik COVID-19. Pengabdian ini menggunakan analisis situasi dimana dalam mengumpulkan informasi data mengenai pembelajaran PKn dan IPS di tengah Pandemi Covid-19 yang relevan. Hasil dalam pengabdian kepada masyarakat, menunjukkan bahwa dampak COVID-19 terhadap pembelajaran daring PKn dan IPS di Sekolah Menengah Pertamabelum terlaksanakan dengan cukup baik. Hal ini dapat dilihat dari kesiapan implementasi pembelajaran daring PKn dan IPS di Sekolah Menengah Pertama, serta kreativitas dalam pembelajaran PKn dan IPS pada masa Ânew normal yang dilaksanakan oleh guru harus ditingkatkan. Sedangkan dalam pembelajaran pada masa new normal sangat diperlukan kerjasama antara guru, peserta didik dan orang tua dalam belajar di rumah.